Temperature and fuel availability control fire size/severity in the boreal forest of central Northwest Territories, Canada. (15th December 2020) - Gaboriau, Dorian M.; Remy, Cécile C.; Girardin, Martin P.; Asselin, Hugo; Hély, Christelle; Bergeron, Yves; Ali, Adam A.
Abstract: The north-central Canadian boreal forest experienced increased occurrence of large and severe wildfires caused by unusually warm temperatures and drought events during the last decade. It is, however, difficult to assess the exceptional nature of this recent wildfire activity, as few long-term records are available in the area. We analyzed macroscopic sedimentary charcoal from four lakes and pollen grains from one of those lakes to reconstruct long-term fire regimes and vegetation histories in the boreal forest of central Northwest Territories. We used regional estimates of past temperature and hydrological changes to identify the climatic drivers of fire activity over the past 10, 000 years. Fires were larger and more severe during warm periods (before ca. 5000 cal yrs. BP and during the last 500 years) and when the forest landscape was characterized by high fuel abundance, especially fire-prone spruce. In contrast, colder conditions combined with landscape opening (i.e., lower fuel abundance) during the Neoglacial (after ca. 5000 cal yrs. BP) were related with a decline in fire size and severity. Fire size and severity increased during the last five centuries, but remained within the Holocene range of variability. According to climatic projections, fire size and severity will likely continue to increase in central Northwest Territories in response to warmer conditions, but precipitation variability, combined with increased abundance of deciduous species or opening of the landscape, could limit fire risk in the future. Highlights: Past fire regimes in Northwest Territories inferred from lake sediment charcoal. Highest fire size/severity ( FS index) during warm periods. Higher fire activity under warm climate and high spruce abundance. Lower FS index after ca. 4000 cal yrs. BP following landscape opening. FS index of the last five centuries within the Holocene range of variability.